Mesodermal Wnt2b signalling positively regulates liver specification - Ober, Elke A.; Verkade, Heather; Field, Holly A.; Stainier, Didier Y. R. (Nature, 2006)
Endodermal organs such as the lung, liver and pancreas emerge at precise locations along the primitive gut tube. Although several signalling pathways have been implicated in liver formation, so far no single gene has been identified that exclusively regulates liver specification. In zebrafish, the onset of liver specification is marked by the localized endodermal expression of hhex and prox1 at 22 hours post fertilization. Here we used a screen for mutations affecting endodermal organ morphogenesis to identify a unique phenotype: prometheus (prt) mutants exhibit profound, though transient, defects in liver specification. Positional cloning reveals that prt encodes a previously unidentified Wnt2b homologue. prt/wnt2bb is expressed in restricted bilateral domains in the lateral plate mesoderm directly adjacent to the liver-forming endoderm. Mosaic analyses show the requirement for Prt/Wnt2bb in the lateral plate mesoderm, in agreement with the inductive properties of Wnt signalling. Taken together, these data reveal an unexpected positive role for Wnt signalling in liver specification, and indicate a possible common theme for the localized formation of endodermal organs along the gut tube. © 2006 Nature Publishing Group.
Created from Fastlane, Scopus look-up